St. Lucia : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
St. Lucia showed strong growth performance owing to its strong investment in tourism infrastructure. Executive Directors commended the prudent public debt management and sound banking system. They underscored the need for fiscal consolidation and steps to promote domestic investment and labor market flexibility. They appreciated the well-designed disaster prevention and mitigation framework, and urged the need to reduce unemployment, reverse the rapid rise in public debt, and encouraged authorities to improve the timeliness and accuracy of data for economic analysis and policymaking.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet